Torsional behaviors of polymer-infiltrated carbon nanotube yarn muscles studied with atomic force microscopy1. Issue 6 (14th February 2015) - Kwon, Cheong Hoon; Chun, Kyoung-Yong; Kim, Shi Hyeong; Lee, Jae-Hyeok; Kim, Jae-Ho; Lima, Márcio D.; Baughman, Ray H.; Kim, Seon Jeong
<x xml:space="preserve">Abstract</x> Torsional behaviors of polymer-infiltrated carbon nanotube (CNT) yarn muscles have been investigated with molecular architecture by using atomic force microscopy (AFM).